His bundle pacing – a new word in technology of pacing and treatment of heart failure - Ya.V. Skybchyk; Ye.V. Zhytyns’kiy; О.М. Grytsay; V.О. Kuts; О.J. Zharinov (Кардіохірургія та інтервенційна кардіологія)
The article presents review of the literature, clinical studies and current guidelines for the usage of His bundle pacing – a new method of treatment of bradycardia and heart blockades. Despite certain temporary limitations – lack of results of the large randomized trials, necessity of the special surgeon's experience in implantation of the electrode, there are reasons to consider His bundle pacing as a promising alternative to the existing methods of treatment of bradyarrhythmias (e.g. classic right ventricular pacing, cardiac resynchronization therapy), particularly in patients with a predicted high (> 40 %) percentage of right ventricular pacing and decreased left ventricular systolic function.